Dietary Omega-3 intake may slow prostate cancer progression and reduce mortality risk: evidence from prostate, lung, colorectal, and ovarian cancer screening trial - Shu, Xinru; Lin, Jiayi; Yao, Ling; Liu, Shun; Chen, Qingquan; Wang, Honggeng; Wang, Liangming (Frontiers in Nutrition, 2025)
BackgroundProstate cancer is the second most prevalent malignant cancer globally and the fifth leading cause of cancer-related mortality. Omega-3 PUFAs [including eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA)] may mitigate prostate cancer risk through various molecular mechanisms, such as inhibiting pro-inflammatory eicosanoid production via COX-2 pathway, regulating apoptosis and autophagy, and potentially influencing other signaling pathways like NF-κB. However, existing studies have reported inconsistent findings regarding the effects of Omega-3 fatty acids on prostate cancer, and there is limited large-scale longitudinal data exploring the dose-response relationship.MethodsThis study utilized data from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Screening Trial to investigate the associations between Omega-3 (EPA, DPA, DHA) intake from dietary sources and the risk of prostate cancer and mortality. Omega-3 fatty acid intake was assessed via the Dietary History Questionnaire (DHQ). Multivariate Cox proportional hazards regression models, adjusted for key confounders including age, race, BMI, family history, PSA levels, comorbidities, and lifestyle factors, were employed alongside restricted cubic spline (RCS) analysis to account for potential confounding factors. A total of 30,552 male participants aged 55–74 years were included, with a median follow-up time of ≥7 years.ResultsThe results indicated a linear relationship between Omega-3 fatty acid intake and the overall risk of prostate cancer (HR for highest vs. lowest quintile: 0.90, 95% CI: 0.81–1.00, P = 0.053). For prostate cancer mortality, a non-linear relationship was observed (Pnon − linearity = 0.009). The risk of death decreased as intake increased below 0.4 g/d, with a hazard ratio of 0.67 (95% CI: 0.49–0.91, P = 0.011) for the second quintile compared to the lowest quintile. However, intake exceeding this threshold was associated with an increased risk (HR for highest quintile: 0.70, 95% CI: 0.52–0.95, P = 0.021). The RCS analysis revealed a potential U-shaped association for mortality risk, with the lowest risk corresponding to an intake range of ~0.15–0.40 g/d.ConclusionIncreased dietary intake of Omega-3 fatty acids has been associated with a reduced risk of prostate cancer. However, the association with mortality risk showed a threshold effect, with intakes below 0.4 g/day reducing mortality and higher intakes potentially increasing risk.